The Manfaat Larutan Vitamin C dan Vitamin E yang Distabilkan Ferulic Acid pada Kulit Manusia - Muhammad Hasta Hendarto (Yayasan Pendidikan Medika Indonesia, 2022)
The skin is the outermost organ that is directly exposed to a prooxidative environment and is equipped with a complex system of antioxidants and enzymes, including redox active antioxidant tissues. Antioxidants are potentially an important group of pharmacological agents capable of preventing and reducing the severity of skin damage caused by various things, including UV rays. To know the benefits of a solution of vitamin C and vitamin E stabilized by ferulic acid on human skin using a method that is a study of literature from an international journal by summarizing the topics discussed and comparing the results presented in the article. The result is a new formulation method that makes it possible to increase the skin's protection against UV damage using topical vitamin C and E stabilized by ferulic acid. Ferulic acid itself has many uses for human skin, namely anti-inflammatory, anticancer, photoprotective agent (sunscreen), delaying the photoaging process of the skin, and brightening components.